Estimation of the profitability of a small-scale commercial wind turbine in Costa Rica - Matarrita-Chaves, Rosa (2022)
Renewable energies are increasingly participating in the electricity matrix in Costa Rica. This paper determined the profitability of installing a small-scale commercial wind turbine in different locations in Costa Rica. It used historical information from the wind speed recorded by National Meteorological Institute in 36 stations across the country, at 10 meters above the ground. This information was combined with the power diagram of the commercial turbine and the annual energy production that can be expected in each location was determined, with this information the estimated savings using the cost of energy in Costa Rica was obtained, besides the net present value (NPV) and the internal return rate (IRR) of this type of investment were calculated. It was obtained that, of the 36 stations studied, 15 have wind resource conditions with the potential to produce more than 1000 kWh/year which represents maximum annual savings of $ 785. Because the characteristics of the wind resource in the analyzed points in Costa Rica and the cost of available electricity, although the country bets on renewable energies, it is not economically profitable to install small-scale commercial turbines in the localities and heights above the ground that were considered, it is recommended to study alternatives such as: generate studies of the wind resource at low altitudes to identify more windy locations, consider towers of greater height or use turbines designed specifically for the wind resource shown in this research.